Analisis Pertanggungjawaban Hukum Debitur Wanprestasi Terhadap Kreditur Yang Menerapkan Alasan Wabah Covid-19 Sebagai Force Majeure - Selvi Apriliya (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This research is normative legal research conducted by reviewing and analyzing library materials. This research refers to the legal norms contained in the legislation and court decisions as well as the norms that live and develop in society. In this study, there are regulations issued by the competent government and local and national government policies that impose lockdowns or social distancing, restrictions on entry routes between regions, and ask the whole community to stay at home or work from home (work from home). house) directly hinders the performance of achievements or obligations in a contract agreement, thus causing this to be classified as a state of coercion or force majeure. Based on the results of the study, it can be understood that debtors who default on creditors during the Covid-19 outbreak using force majeure reasons so that they are free from the responsibility to make achievements, there must be elements of force majeure according to Article 1245 of the Civil Code and the debtor is obliged to prove it. With the POJK No. 11/POJK.03/2020 concerning National Economic Stimulus as a Counter-cyclical Policy on the Impact of the Spread of Coronavirus Disease 2019 and POJK No. 14/POJK.05/2020 concerning Counter-cyclical Policy on the Impact of the Spread of Corona Virus Disease 2019 for Non-Bank Financial Services Institutions. This regulation authorizes banking financial institutions or financing institutions to provide “credit relaxation”, in which credit relaxation itself is the granting of concessions related to credit payments amid Covid-19.